Geometric integration methods of high order for gradient systems - Hernández-Solano, Yadira; Atencia-Ruiz, Miguel Alejandro (My University, 2014)
We propose the higher order extension of numerical methods that preserve the energy-diminishing feature of a system with Lyapunov function.
Keywords: Lyapunov, Funciones de